DIGITAL ECONOMY DEVELOPMENT ISSUES IN THE SOCIO-ECONOMIC ENVIRONMENT - Anatolevna Baryshnikova, Natalia; Vladimirovna Glinkina, Olga; Olegovna Kozhina, Veronika; Yurievna Nikolskaya, Elena; Petrovich Kulgatchev , Ivan (Revista Inclusiones, 2020)
The article deals with the analysis of the digital economy development issues in the socio-economic environment. It is established that the digital economy is a new type of economic relations, which is already present in all sectors of the global market and is actively developing. It is revealed that the digital economy can soon become a leading segment, a growth and development driver of the socioeconomic system in general. This is because the digital economy has some advantages over material commodity-money exchange, such as the prompt delivery of goods, or almost instantaneous provision of services. Another advantage of the digital economy is the lower cost of producing and executing transactions. It is proved that one of the key advantages of the digital economy over the traditional one is that electronic goods exist in virtual form and are practically inexhaustible.